Activation of TRPV4 Regulates Respiration through Indirect Activation of Bronchopulmonary Sensory Neurons - Gu, Qihai (David); Moss, Charles R.; Kettelhut, Kristen L.; Gilbert, Carolyn A.; Hu, Hongzhen (Frontiers in Physiology, 2016)
Transient receptor potential vanilloid receptor 4 (TRPV4) is a calcium-permeable non-selective cation channel implicated in numerous physiological and pathological functions. This study aimed to investigate the effect of TRPV4 activation on respiration and to explore the potential involvement of bronchopulmonary sensory neurons. Potent TRPV4 agonist GSK1016790A was injected into right atrium in anesthetized spontaneously breathing rats and the changes in breathing were measured. Patch-clamp recording was performed to investigate the effect of GSK1016790A or another TRPV4 activator 4a-PDD on cultured rat vagal bronchopulmonary sensory neurons. Immunohistochemistry was carried out to determine the TRPV4-expressing cells in lung slices obtained from TRPV4-EGFP mice. Our results showed that right-atrial injection of GSK1016790A evoked a slow-developing, long-lasting rapid shallow breathing in anesthetized rats. Activation of TRPV4 also significantly potentiated capsaicin-evoked chemoreflex responses. The alteration in ventilation induced by GSK1016790A was abolished by cutting or perineural capsaicin treatment of both vagi, indicating the involvement of bronchopulmonary afferent neurons. The stimulating and sensitizing effects of GSK1016790A were abolished by a selective TRPV4 antagonist GSK2193874 and also by inhibiting cyclooxygenase with indomethacin. Surprising, GSK1016790A or 4a-PDD did not activate isolated bronchopulmonary sensory neurons, nor did they modulate capsaicin-induced inward currents in these neurons. Furthermore, TRPV4 expression was found in alveolar macrophages, alveolar epithelial and vascular endothelial cells. Collectively, our results suggest that GSK1016790A regulates the respiration through an indirect activation of bronchopulmonary sensory neurons, likely via its stimulation of other TRPV4-expressing cells in the lungs and airways.